2008
DOI: 10.1186/1479-5868-5-26
|View full text |Cite
|
Sign up to set email alerts
|

Lack of agreement between measured and self-reported distance from public green parks in Glasgow, Scotland

Abstract: Background: Reviews have reported mixed findings for associations between physical activity and proximity to a range of environmental resources. Initially most studies used self reported proximity, but more are now using GIS techniques to measure proximity objectively. We know little about the extent of agreement between self reported and directly measured proximity of the same resource.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
74
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(85 citation statements)
references
References 31 publications
(22 reference statements)
10
74
0
1
Order By: Relevance
“…Recent studies have suggested that parks, squares, and other green spaces for recreation in neighborhoods are important places for people to be more physically active 35 , especially in urban areas where access to green spaces is more limited 36 . There is also evidence that improved availability and access to green spaces for recreation in urban areas can be an effective public health measure, Table 3 Description of variables in the social environment and built environment by coverage area.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that parks, squares, and other green spaces for recreation in neighborhoods are important places for people to be more physically active 35 , especially in urban areas where access to green spaces is more limited 36 . There is also evidence that improved availability and access to green spaces for recreation in urban areas can be an effective public health measure, Table 3 Description of variables in the social environment and built environment by coverage area.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to green space has been identified as a factor reducing health inequalities in the UK (Mitchell and Popham, 2007). Physical activity within green spaces has been investigated as a possible mechanism behind the relationship between access to green space and salutogenic effects (Maas et al, 2006(Maas et al, , 2008Macintyre et al, 2008;Coombes et al, 2010;Koohsari et al, 2015;Hunter et al, 2015;Buck et al, 2015). In contrast, outside of environmental psychology, the health-related value of blue space and the role of physical activity within blue spaces have attracted much less attention to date (Herzog, 1984).…”
Section: Activity Spacesmentioning
confidence: 99%
“…This result supports previous findings suggesting that self-reported access to urban parks does not accurately reflect objectively measured access (Macintyre et al, 2008b).…”
Section: Discussion Conclusion and Further Studiessupporting
confidence: 82%